Can Center-Based Care Reduce Summer Slowdown Prior to Kindergarten? Exploring Variation by Family Income, Race/Ethnicity, and Dual Language Learner Status. (April 2021) - McCormick, Meghan P.; Pralica, Mirjana; Guerrero-Rosada, Paola; Weiland, Christina; Hsueh, Joann; Condliffe, Barbara; Sachs, Jason; Snow, Catherine
This study examines growth in language and math skills during the summer before kindergarten; considers variation by family income, race/ethnicity, and dual language learner status; and tests whether summer center-based care sustains preschool gains. Growth in skills slowed during summer for all children, but the patterns varied by domain and group. Non-White and dual language learner students showed the largest drop-off in language skills during summer. Lower-income students demonstrated slower summer growth in math skills than their higher-income peers. Students enrolled in summer center-based care had faster growth in math skills than those who did not attend care. Yet lower-income students who attended center-based care showed slower growth in language skills during summer than similar nonattenders. Implications are discussed.